Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1614/ipsm-d-11-00067.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Stakeholder Perspectives on Invasive Plants to Inform Risk Analysis

Abstract: Conservation and land management decisions often are based primarily on natural science, but could be more successful if human influences were effectively integrated into decision making. This is especially true for efforts to manage invasive plants, whose arrival is usually the product of deliberate human introduction. Risk-assessment models that predict the probability that a nonnative plant will naturalize or invade are useful tools for managing invasive plants. However, decisions based on such models could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Private crop or pest consultants were identified as information sources by only a few respondents. Most members of the Connecticut Nursery and Landscape Association informed themselves about invasive plants through trade journals and professional organisations (Gagliardi and Brand 2007), while a study in Iowa (Kapler et al 2012) among conservation professionals, master gardeners, professional horticulturalists and woodland landowners found that the most common sources of information about invasive plants were newspapers, magazines or books (82.3 %), educators or workshop/lectures (81.7 %), conservation professionals (74.8 %), colleagues (63.8 %), and the Internet (60.8 %); plant retailers or nurseries were the least common source of information.…”
Section: Information Provision and Stakeholder Engagementmentioning
confidence: 99%
“…Private crop or pest consultants were identified as information sources by only a few respondents. Most members of the Connecticut Nursery and Landscape Association informed themselves about invasive plants through trade journals and professional organisations (Gagliardi and Brand 2007), while a study in Iowa (Kapler et al 2012) among conservation professionals, master gardeners, professional horticulturalists and woodland landowners found that the most common sources of information about invasive plants were newspapers, magazines or books (82.3 %), educators or workshop/lectures (81.7 %), conservation professionals (74.8 %), colleagues (63.8 %), and the Internet (60.8 %); plant retailers or nurseries were the least common source of information.…”
Section: Information Provision and Stakeholder Engagementmentioning
confidence: 99%
“…In contrast, 88% of residents in north central Colorado had heard or read about invasive plants, a high level of awareness that the authors attribute to the fact that weeds are a high-profile issue in this region (Daab and Flint 2010). Similarly, in Iowa, 87% of key stakeholders agreed that invasive plants are a problem and 88% agreed that we have a responsibility to manage them (Kapler et al 2012). In Montana, 76% of residents agreed that noxious weeds are a serious or very serious problem, but 67% reported that they knew little or nothing about noxious weeds; however, 80% could identify a specific problem associated with invasive plants (Sheley et al 1996).…”
mentioning
confidence: 96%
“…On the other hand, they benefitted from fuel wood and building timber (De Wit et al 2001). Such situations have led to the recognition of a need for a framework to document the different consequences of an IAS for different groups of stakeholders (Stoll-Kleemann and Welp 2006, Binimelis et al 2007, Kapler et al 2012 and recently a few attempts have been made to develop applications which incorporate stakeholders (Cook and Proctor 2007, Hurley et al 2010, Liu et al 2011, De Lange et al 2012. Parker et al (1999) developed a framework to assess the ecological effect of IAS, arguing that the total effect of an invader includes three fundamental dimensions: range, abundance, and the per-capita or per-biomass effect of the invader, i.e.…”
mentioning
confidence: 99%